Penonjolan Identitas Melayu Islam oleh Pemerintah dan Masyarakat Riau - Hasse Jubba; Muhammad Rafi; Zuly Qodir (Sospol : Jurnal Sosial Politik, 2021)
This article aims to explain the efforts of the government and the people of Riau in promoting Islamic Malay identity. Through observation, literature study and documentation study, several efforts were found to support the continuity of Malay identity amidst various challenges today. The concept of identity politics is used to analyze the above problems and it is found that there are three construction processes of a social identity which include legitimate identity, resistant identity, and project identity. This paper finds the finding that the efforts to emphasize Islamic Malay identity by the government and the people of Riau are carried out in three stages. First, efforts to legitimize the Malay identity through the formation of the Riau Customary Institution (LAM) which is dedicated to protecting and preserving the heritage of the Malay symbol and in cooperation with the Riau Provincial Government. Second, efforts to fight against the negative stigma attached to Malay culture in the past. Third, the identification of Malay as Islam and vice versa through the promotion of Malay as an effort to ward off previous negative views and to affirm the existence of Islamic Malay culture in Riau.